Forensic Engineering 2022. selected papers from the Ninth Congress on Forensic Engineering, November 4-7, 2022, Denver, Colorado - Liu, Rui (Structural engineer); Mulea, Carmen C.; Parfit, M. Kevin; Cavalline, Tara (American Society of Civil Engineers, 2022)
Selected papers from the Ninth Congress on Forensic Engineering, held in Denver, Colorado, November 4-7, 2022. This collection contains 9 peer-reviewed papers on the founding and development of CROSS in the UK and its expansion internationally. Included are contributions from the UK, Australasia, the US, and Germany, and span both structural and fire safety. The Collaborative Reporting for Safer Structure's unique role in the system of assuring structural safety is described and the tremendous potential for even greater impact internationally is envisioned.